Saccharomyces Cerevisiae cell wall dietary supplementation on the performance and intestinal mucosa development and integrity of broiler chickens vaccinated against coccidiosis - Luquetti, BC [UNESP] (2012)
This study was carried out to verify if Saccharomyces cerevisiae cell wall (SCCW) dietary supplementation (0.2%) was capable of protecting the intestinal mucosa of broiler chickens vaccinated against coccidiosis. Body weight gain, feed intake, feed conversion and intestinal mucosa morphometric parameters and epithelial loss were evaluated. In the experiment,400 day-old male chicks were distributed according to a completely randomized design in a 2x2 factorial arrangement. The following treatments were applied: T1 - no vaccination/ no SCCW supplementation; T2 - no vaccination/SCCW supplementation; T3 - vaccination/no SCCW supplementation; and T4 - vaccination/SCCW supplementation to four replicates of 25 birds each. Birds were vaccinated on the first day of age using a spray vaccine (Coccivac B®, Coopers), containing E. acervulina, E. maxima, E. mivati and E. tenella. S. cerevisiae cell wall was supplied from the first day of age. Live performance, intestinal morphometric parameters and epithelial loss were evaluated at 14, 21 and 28 days of age. Performance was affected by vaccination only at 21-days of age, when body weight gain was reduced in the vaccinated birds, but no body weight difference was observed on day 28. Vaccine also increased the crypt depth (p<0.05) in the duodenum and jejunum, suggesting a high cell activity in the crypt:villus transition area to maintain the epithelial cell turnover. Villi number/area (103,269 µm²) was not affected (p>0.05) by vaccine or cell wall supplementation, and epithelial loss was more pronounced in the duodenum and jejunum. In conclusion, the findings of this study suggest that S. cerevisiae cell wall supplementation may be an useful management tool to maintain the intestinal integrity of broilers vaccinated against coccidiosis.